One-Shot Pulse Boost Converter-Based Inductor-Synchronized Piezoelectric Energy Harvester - Sutikno, Tole; Pradana, Muhammad Sukmadika; Pamungkas, Anggit (Universitas Ahmad Dahlan, 2024)
In this paper, we aim to review current methods of energy harvesting, focusing on piezoelectric energy. To optimize the use of piezoelectric devices in applications, a model is needed to observe the performance generated from piezoelectricity. To achieve better performance, the rectifier and capacitor systems are connected to a boost converter circuit. Another method is to use the Synchronized Switch Harvesting Inductor (SSHI) method. This method implements a stand-alone switching technique based on transistors and rectifier diodes and does not require an external power supply. This research creates an electric energy harvesting floor device by utilizing piezoelectricity in the form of a harvester, which aims to find out how piezoelectric works and to obtain a circuit with the most efficient characteristics as a piezoelectric power generator using SSHI and a boost converter. This study compares the characteristics of series, parallel, and series-parallel circuits on the floor of the most optimal piezoelectric energy harvester to generate voltage. The results of the data collection were based on the number of steps on the floor of the 16-piece piezoelectric energy harvester with a series-parallel circuit configuration connected with an SSHI circuit and without an SSHI circuit. In this test, the resulting voltage output is a DC voltage with an input step of 60 times the step on piezoelectricity. In this paper, an energy harvester using the SSHI circuit provides a more stable voltage on the harvester floor than a boost converter by providing 16 piezoelectric pieces arranged in series parallel. A floor energy harvester with a series-parallel configuration connected to SSHI gets the most optimal result compared to using a boost converter.